1996
DOI: 10.1161/01.res.79.3.560
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Expression of E- and P-Selectins In Vivo

Abstract: A novel technique involving radiolabeled monoclonal antibodies was used to characterize and compare the expression of E- and P-selectin on unstimulated, histamine-challenged, and endotoxin-challenged endothelial cells in various tissues of the mouse. Under unstimulated conditions, E-selectin was absent in all organs, but significant expression of P-selectin was observed in several organs. Histamine induced a rapid time-dependent upregulation of P-selectin, with the largest responses observed in mesentery and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
270
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(293 citation statements)
references
References 32 publications
18
270
0
5
Order By: Relevance
“…Expression of the adhesion molecules P-selectin and VCAM-1 were quantified using a modified dualradiolabeled Ab technique (21,24). The Abs RB40.34 (against P-selectin) and 429 (MVCAM.A) (against VCAM-1) were labeled with 125 I.…”
Section: Quantitation Of Endothelial Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of the adhesion molecules P-selectin and VCAM-1 were quantified using a modified dualradiolabeled Ab technique (21,24). The Abs RB40.34 (against P-selectin) and 429 (MVCAM.A) (against VCAM-1) were labeled with 125 I.…”
Section: Quantitation Of Endothelial Activationmentioning
confidence: 99%
“…The Abs A110-1 (a rat IgG1, isotype standard) and R35-95 (a rat IgG2a, isotype control Ig) were labeled with 131 I. In both cases, the Abs were labeled using the IodoGen method, as previously described (21,24). A110-1 and R35-95 were used to detect nonspecific binding in the murine system.…”
Section: Quantitation Of Endothelial Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that in vivo P-selectin expression increases in mesenteric venules of the rat 6 hr after abdominal irradiation with 10 Gy [12]. The heterogeneity in constitutive and induced P-selectin expression in the different vascular beds [13] suggests that its role in acute inflammation may depend on the tissue in which damage occurs.…”
Section: Introductionmentioning
confidence: 99%
“…There are several other surface markers that also show promise as EC targets such as intercellular adhesion molecule 1 (ICAM-1), lectin-like oxidized LDL receptor (LOX-1), and P-selectin (18). P-selectin is constitutively expressed on vascular endothelium with lung ECs having the highest level of expression.…”
Section: Surface Properties and Uptake Mechanisms Of Macromolecules Omentioning
confidence: 99%